Socio-Cultural Factors Backgrounding Islamic Legal Thought - Hendra Dwi Aditya; Muthoifin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This article discusses the influence of socio-cultural factors on several Islamic legal products in Indonesia.Socio-cultural elements in the history of Islamic law by analyzing some examples of the results of scholarly thoughts in the form of fiqh, fatwas, court decisions, and laws applied in Islamic countries Islamic legal thought products. The role of Islam in Indonesia's social, cultural, and economic dynamics developed through a long struggle, where Hindu/Buddhist and Christian influences were accompanied by changes in the socio-cultural system. Islam remains a dominant part of the nation today. Because it provides a space that separates the sacred from the profane, there is still a secular influence , albeit culturally and psychologically problematic. On the other hand, the pure teachings of Islam are those that liberate people from dependence on secular culture. Numerically the background to the formation of social order in society is that Islam plays a dominant role, but in fact, due to the acculturation of past cultures and the reality of modern national life, Islam has signs of being shifted. Otherwise, Islam in Indonesia will be used as a stamp of power to prop up a corrupt capitalist government.